2019
DOI: 10.1017/s0144686x19000783
|View full text |Cite
|
Sign up to set email alerts
|

Filial piety and intergenerational ambivalence among mother–adult child dyads in rural China

Abstract: This study examines the relationship between filial piety (adult children's filial behaviours and attitudes as well as elderly mothers’ overall evaluation of children's filial piety) and elderly mothers’ reports of intergenerational ambivalence (positive feelings, negative feelings and combined ambivalence) in rural China. We analysed the data from a survey in 2016 covering 2,203 adult children and 802 elderly mothers in Sichuan Province using a two-level mixed-effects modelling analysis. The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Obedience of parents, for example, can be seen as an ‘Extreme Principle’ (Sin, 2019 a ) or a ‘strong principle’ (Sin, 2019 b ). Nevertheless, in today's Chinese societies, including the Canadian immigrant community, it does not refer to parents’ absolute authority over children, or children's unconditional obedience to parents, or children's obligation to support parents at any cost (Canda, 2013; Yeh et al , 2013; Q Guo et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Obedience of parents, for example, can be seen as an ‘Extreme Principle’ (Sin, 2019 a ) or a ‘strong principle’ (Sin, 2019 b ). Nevertheless, in today's Chinese societies, including the Canadian immigrant community, it does not refer to parents’ absolute authority over children, or children's unconditional obedience to parents, or children's obligation to support parents at any cost (Canda, 2013; Yeh et al , 2013; Q Guo et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…, 2020). This concept is often used to explain the complexity of family relations under affective and cognitive conflict (Connidis and Mcmullin, 2002; Guo et al. , 2019; Hua et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to competing needs for independence and connection, intergenerational ambivalence theory argues that intergenerational relationships can be close as well as irritating (Fingerman et al, 2020). This concept is often used to explain the complexity of family relations under affective and cognitive conflict (Connidis and Mcmullin, 2002;Guo et al, 2019;Hua et al, 2020;L€ uscher and Pillemer, 1998). Studies have found that the positive and negative effects of intergenerational ambivalence will have a negative impact on the mental health of the elderly, and may lead to guilt (Kalmijn, 2020).…”
Section: Complex Feelings Between Generationsmentioning
confidence: 99%
“…As these individuals age, their decreased physical functioning impairs their ability to farm; thus, they lose their primary source of income, and struggle to remain self-sufficient. Traditional Chinese Confucian culture emphasizes filial piety, which means older adults mainly rely on their adult children for their support and care [30]. As a result, rural older adults whose children work in cities often feel there is no one they will be able to rely on in the future.…”
Section: The Main Findingsmentioning
confidence: 99%